A New Type Of Digital Band - Pass Filter - Suprajitno Munadi (Testing Center for Oil and Gas LEMIGAS, 1986)
Digital filtering is mathematical process which provides a means of filtering data numerically. The filtering process can be carried out in the frequency domain to discriminate signal and noise based on the frequency differencesThe digital band-pass frequency filtering has been effectively accomplished using a new type of digital filter. This filter is the result of compolving a boxcar spectral window with a frequency shifted Gaussian function which produces a very smooth transition between the pass-band and the stop-band region. The slope of the filter is controlled by the exponential coefficient of the Gaussian function. For a very narrow pass-band the exponential coefficient also controls the resolution of the filter.Experiments have been done with the Synthetic Vertical Seismic Profiles data to prove the performance of the filter and shows a good results.Â